Supplier Quality from reactive to proactive - Mäkelä, Ari Matti Kalevi (My University, 2015)
Goal of this study is how the supplier quality assurance organization can move from reactive to proactive way of working. An organizational change inside the case company is the starting point for this study. As the researcher is working in the organization during the study period an action analytical research method is chosen. Case study approach is chosen as the researcher is inside the organization and observes the current situation in contrast to existing practices and guidelines while applying chosen theories to achieve given targets. In this study a strategy is created for the supplier quality assurance department. From strategy a development plan is induced. Development plan includes consideration on responsibilities and communication on non-conformity handling in the case company. For the incoming inspection workshop methods to reduce lead time are done in a form of layout development project. Performance measurement indicators are created to adjust and confirm the effectiveness of several on-going development projects. Few main points for further development are given for the management to consider. This study gives an overall picture of a one way to establish a new strategy and initiate needed development projects to meet the productivity targets given by company’s management.
Keywords: Supplier quality assurance; performance measurement; strategy; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|